2020
DOI: 10.1101/2020.08.28.269886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoencapsulation of clove oil and study of physico-chemical properties, cytotoxic, haemolytic and antioxidant activities

Abstract: The therapeutic properties of clove oil is known for centuries, however, the pungent nature, chemical instability and low water solubility impose limitations in harnessing its therapeutic potential. Hence, nanoencapsulation of clove oil was performed to overcome the above constraints and control its in-vitro release. The stability of nanoemulsion depends on various factors where the surfactant and its hydrophile/lipofile balance (HLB) play a key role. The non-ionic surfactants Tween 20, 40 and 80 with HLB of 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Moreover, sharp peaks at ~1700, 1610, and 1465 cm −1 were also found with Eug, which can be due to the C = C stretching of the aromatic moiety. These data were consistent with previous reports [ 51 , 52 ]. Similarly, the same peaks were also observed in the Eug-NE spectrum ( Fig 3B ), indicating the absence of a chemical interaction between Eug and Tween 20 in the nanoemulsion formulation.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, sharp peaks at ~1700, 1610, and 1465 cm −1 were also found with Eug, which can be due to the C = C stretching of the aromatic moiety. These data were consistent with previous reports [ 51 , 52 ]. Similarly, the same peaks were also observed in the Eug-NE spectrum ( Fig 3B ), indicating the absence of a chemical interaction between Eug and Tween 20 in the nanoemulsion formulation.…”
Section: Resultssupporting
confidence: 94%
“…However, they noticed bands from O–H vibrations, which was not observed in our study. Similarly, Nagaraju et al [ 35 ] observed the presence of the hydroxylated group in samples of clove oil. It indicated directly that strong differences between the samples from various sources may occur.…”
Section: Resultsmentioning
confidence: 83%
“…OEO is mainly composed of carvacrol (57.4–69.6%), thymol (30.3–42.8%), cymene (17.7–51.3%), and terpinene (2.63–6.15%) [ 13 ]. These bioactive compounds have strong antibacterial, antifungal, antiparasitic, cytotoxic, and antioxidant activity [ 14 , 15 , 16 , 17 , 18 ]. However, the high volatility, sensitivity, and relatively low stability of EOs may minimize their performance when intended for use as pharmaceutical agents [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, incorporation of EOs into nanoliposomes holds a great strategy to improve bioavailability, minimize toxicity, and prevent the degradation of EOs for therapeutical proposes [ 13 , 14 , 15 ]. Thus, the combination of essential oils with engineered materials has made it possible to enhance EO features by protecting them from external factors, therefore avoiding degradation, oxidation, and reducing their volatility [ 17 ].…”
Section: Introductionmentioning
confidence: 99%